1988
DOI: 10.1002/jhet.5570250552
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the chemistry of pyrimido[1,2‐B]pyridazinones

Abstract: On reacting the 3‐aminopyridazines 1a,d,e with dimethyl acetylenedicarboxylate (DMAD), the pyrimido[1,2‐b]pyridazin‐2‐(2H)‐ones 2e‐g, whereas starting from 1f, the 4(4H)‐ones 5a and 3b,d were prepared. In the 2(2H)‐one series, the reactions of 2b with various amino compounds resulted in various types of products. The reaction of N‐methylaminopyridazines 1g,h with DMAD led to the endo‐N‐substituted derivatives 8a,b, whereas 1h with diethyl ethoxymethylenemalonate (DEM) gave the exo‐N‐substituted compound 1k. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Pyridazino[2,3-b]pyrimidines (44) (Fig. 42) may be obtained from DEEM in diphenyl ether or by thermal method [171]. Chen and Shan [172] prepared 4-oxopyrimidino[1,2-a] pyrimidino-3-carboxylates (45) (Fig.…”
Section: Bicyclic Systemsmentioning
confidence: 99%
“…Pyridazino[2,3-b]pyrimidines (44) (Fig. 42) may be obtained from DEEM in diphenyl ether or by thermal method [171]. Chen and Shan [172] prepared 4-oxopyrimidino[1,2-a] pyrimidino-3-carboxylates (45) (Fig.…”
Section: Bicyclic Systemsmentioning
confidence: 99%
“…However, besides electron donation, further factors may be present, as ring closure led to the formation of the desired pyrimido[1,2- b ]pyridazin-2-one derivative only in the case of the hydroxy-substituted starting compound ( 64a ). The morpholino group yielded 2-oxo-4-carboxylate analogues, similar to the chloro-substituted derivative ( 64b,c , Scheme 22 ) [ 75 , 76 ]. The research group also noted this difference as an anomaly, based on previous work [ 77 ].…”
Section: Synthesis Of Functionalized and Heteroatom Containing Kyna Derivativesmentioning
confidence: 99%
“…In 1983, Mátyus et al reported a one-step access to compound 5 by direct condensation of a substituted 3-aminopyridazine with methyl propiolate or dimethyl acetylenedicarboxylate in refluxing ethanol (Scheme 1). [5][6][7] The latter is currently the most commonly used method for the preparation of the pyrimido [1,2b]pyridazin-2-one core.…”
mentioning
confidence: 99%
“…Additionally, we attempted to prepare compounds 10 using a one-pot procedure starting from 3-amino-6-chloropyridazine and ethyl 4,4,4-trifluorobut-2-ynoate (6). Indeed, the condensation of 3-amino-6-chloropyridazine and 6, performed under the same conditions as those described above, followed by in situ addition of previously employed representative nucleophiles (i.e., primary and secondary amines and a thiol), led to the formation of compounds 10a, 10f and 10h in yields comparable to those obtained via the two-step procedure ( Table 3).…”
mentioning
confidence: 99%